Relationship between financial literacy and quality of life among elderly in rural area in Pahang / Nurul A'ina Fitriah Azhar - Azhar, Nurul A'ina Fitriah (Faculty of Sport Sciences and Recreation, 2020)
The aim of this study is to investigate the relationship between financial literacy and quality of life among elderly. This study involved the elderly in Maran, Jerantut and Kuala Lipis (n=300). Researcher will briefly be explained to elderly and then answered the Basic Financial Literacy questionnaire and CASP-19 questionnaire. Data analyses used in this study were Spearman's rho correlation test and Mann Whitney U test. Study shows non-significant differences between financial literacy and quality of life among elderly in data collected with value of .355 (p <0.05). There are no significant differences between financial literacy and quality of life among elderly. The researcher found there was negative correlation between financial literacy and quality of life. Therefore, family support for the elderly people had become a very important issued in examining the overall well-being of the elderly